Enhanced Biosynthesis of Chlorogenic Acid and Its Derivatives in Methyl-Jasmonate-Treated Gardenia jasminoides Cells: A Study on Metabolic and Transcriptional Responses of Cells - Liu, Zebo; Mohsin, Ali; Wang, Zejian; Zhu, Xiaofeng; Zhuang, Yingping; Cao, Liming; Guo, Meijin; Yin, Zhongping (Frontiers in Bioengineering and Biotechnology, 2021)
Chlorogenic acid and its derivatives (CQAs) are considered as the important bioactive secondary metabolites in Gardenia jasminoides Ellis (G. jasminoides). However, few studies take an insight into the biosynthesis and regulation of CQAs in the G. jasminoides. In this study, methyl jasmonate (MeJA) was used to enhance CQAs accumulation in the cultured G. jasminoides cells. Moreover, the possible molecular mechanism of MeJA-mediated accumulation of CQAs is also explored. To this end, time-course transcriptional profiles of G. jasminoides cells responded to MeJA was used to investigate the mechanism from different aspects, including jasmonates (JAs) biosynthesis, signal transduction, biosynthesis of precursor, CQAs biosynthesis, transporters and transcription factors. A total of 57069 unigenes were assembled from the clean reads, in which 80.7% unigenes were successfully annotated. Furthermore, comparative transcriptomic results indicated that the differentially expressed genes (DEGs) were mainly involved in JAs biosynthesis and signal transduction (25 DEGs), biosynthesis of precursor for CQAs (18 DEGs), CQAs biosynthesis (19 DEGs) and transporters (29 DEGs). Most of these DEGs showed continuously up-regulated expressions over time, which might activate the JA signal transduction network, boosted precursor supply, and ultimately stimulated CQAs biosynthesis. Additionally, various transcription factors from different TF families also responded to MeJA elicitation. Interestingly, 38 DEGs from different subgroups of MYB family might display positive or negative regulations on phenylpropanoids, especially on CQAs biosynthesis. Conclusively, our results provide an insight into the possible molecular mechanism of regulation on CQAs biosynthesis, which led to a high CQAs yield in the G. jasminoides cells under MeJA treatment.